Mouse insulin-responsive glucose transporter gene: characterization of the gene and trans-activation by the CCAAT/enhancer binding protein. - Kaestner, K H (1990)
Adipose tissue and skeletal and heart muscle, which exhibit insulin-stimulated glucose uptake, express a specific, insulin-responsive glucose transporter. Previously, a cDNA (GT2) encoding this protein was isolated from a mouse 3T3-L1 adipocyte library and was sequenced. Here we report the isolation and characterization of the corresponding mouse gene designated GLUT4. The GLUT4 gene spans 7 kilobases and consists of 11 exons and 10 introns. The start site of transcription was mapped 180 nucleotides upstream of the initial methionine codon. The GLUT4 promoter contains four potential binding sites for the nuclear transcription factor Sp1 as well as a CCAAT box. DNase I footprinting of the GLUT4 promoter with nuclear extracts from undifferentiated and differentiated 3T3-L1 cells revealed that a differentiation-specific nuclear factor binds in the region at position -258 relative to the start site of transcription. Purified CCAAT/enhancer binding protein (C/EBP) was found to bind at the same position. Transient cotransfection into 3T3-L1 preadipocytes of a GLUT4 promoter-chloramphenicol acetyltransferase gene construct that contains the C/EBP binding site, together with a C/EBP expression vector, revealed that C/EBP trans-activates the GLUT4 promoter. We suggest that C/EBP plays an important role in tissue-specific, as well as metabolic, regulation of the insulin-responsive glucose transporter gene.